Innovation and Development in Improving Public Services During the New Normal Era in Indonesia - Kurhayadi Kurhayadi (Journal of Governance, 2022)
Various changes that occurred due to the emergence of COVID-19 and the entry of the new normal era led to the government’s need for innovation and new development in providing public services to the community. This study aims to examine how the government can create innovations and develop various public services in Indonesia in the new normal period. This research will use a qualitative approach using analytical methods. The data in this study was obtained from various studies and studies that are still relevant to this research. This study found that the government has made multiple innovations for the public service sector. The form of these innovations is the focus in the APBN budget to deal with the APBN in such areas as health, education, social, or economic aspects. This is developing following the Industrial Revolution 4.0 era and the paradigm in public administration, which conceptually adopts many practices from private organizations. The government establishes partnerships with private organizations to study and seek innovative ideas in public service.